Trendsetter Komunikasi Di Era Digital: Tantangan Dan Peluang Pendidikan Komunikasi Dan Penyiaran Islam - Taufik Hidayat (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
The importance of communication trendsetters in the context of the digital era, especially in the field of Communication Education and Islamic Broadcasting, is discussed in this journal. With continuously advancing technology, this article explores the challenges faced by educational institutions in integrating communication trendsetters into their curricula. Additionally, the journal highlights opportunities emerging alongside technological developments that can enhance the effectiveness of communication and Islamic broadcasting education. A thorough analysis of these dynamics is expected to provide valuable insights for practitioners, academics, and decision-makers in this field.